The Concept of Integrating Virtual Group (VG) and Agile Supplier Selection (ASS) - Farzad, Tahriri; Zahari, Taha (2010)
Agile Manufacturing (AM) is a new concept in manufacturing intended to improve the competitiveness of firms. In 21st century, businesses in order to overcome their competitors, should be able to handle challenges of demanding customers seeking high quality, low cost products and also become more flexible with their specific and rapid changing needs. One of the recent concepts in support of flexibility for factories is Virtual Group (VG). This concept enables the appropriate application of lean and agile concepts to be combined in a cellular manufacturing for different stages of production with in a factory.Flexibility of the supply chain in manufacturing counters the uncertainty in the decision parameters. A supply chain adapts the changes if it is flexible and agile in nature. Integration of appropriate Agile Suppliers Selection (ASS) and Virtual Group (VG) is proposed in this paper. It is argued that the concept of VG by its own is not sufficient for providing flexibility. Therefore, consideration should be taken towards other factors, such as supplier notices, affecting the factory production line in which VG are used. A combination concept comprising VG and supplier is considered in this model. The significance of this subject relies on the producers who confront variable and standard combination factors, as well as manufacture standard and special products. This paper classifies both VG and supplier groups based on the three concepts: Lean, Agile, and Leagile.